(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Wild and cultivated plants were surveyed in the Kapadokya region of Turkey in 1999, and samples of 23 species were collected. Eleven species new to the Turkish Scale insect fauna were recorded, namely: Phenacoccus pumilus Kiritchenko, Phenacoccus hordei (Lindemann), Atrococcus paludinus (Green), Heliococcus radicicola Goux, Phenacoccus bicerarius Borchsenius, Rhizopulvinaria spinifera Borchsenius, Scytia craniumequinum Kiritchenko, Pulvinaria terrestris Borchsenius, Acanthopulvinaria orientalis (Nassonov), Duplachionaspis noaeae (Hall) and Eriococcus thymi (Schrank).